Identifikasi Best Practice Kepemimpinan Manajemen Pendidikan Agama Islam di Era Persaingan Global - Buhari Luneto; Muh Hasbi (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2023)
The focus of this research is to identify best practice and management of Islamic education in the era of globalization which is full of global competition. The purpose of the research is to prepare Islamic education management that is considered good even though the challenges experienced in the world of education today are various. The research method used is qualitative with a literature review approach. The research data consisted of primary and secondary. Primary in the form of data that is considered almost the same from the title of this article which is found in several journals, both national and international. While secondary data is supporting data from the literature that is related to this article. The data analysis was carried out using an in-depth coding, interpretation and evaluation system of data. The results show that the best practice and management of Islamic education which is considered capable of competing in this era of globalization consists of transformational leadership, training, interactional, and several other leadership styles.